(untitled) (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2014)
The purpose of this study was to develop and test models of the internalization value of organizational culture that appears to determine the characteristics of organizational commitment among employees of PT. Pertamina (Persero) Unit II Dumai Refinery, Indonesia. The internalized of values organizational culture was related to the organizational commitment dimension (affective, normative, and continuance). Likewise, organizational commitment was correlated to the internalized of values organizational culture (clean, competitive, confident, customer focused, commercial, and capable). It seems that higher internalized of values organizational culture associated with higher of commitment in organization, vice versa. Internalized of values organizational culture dimensions interaction showed no greater value than organizational commitment based on sociodemographic variables, this shows demographic factors should know better human resources and cultural values.